Raising the profile of teaching and learning : scientists leading scientists. - Burke da Silva, Karen; Fawcett, Robyn; Hunter, Narelle; Buckley, Pat; Roberts, Michael; Dent, Lindsay; Wood, David; Gannaway, Deanne (Australian Learning and Teaching Council, 2008)
The central idea behind the project Raising the Profile of Teaching & Learning: Scientists Leading Scientists was to enhance the value of science teaching and science education research in South Australia, using a framework in which: Project activities used language, context and exemplars that were highly relevant to academic scientists; Leadership development in science education & scholarship was specifically targeted, and; The conventions of scientific research – conferences, evidence-based activity, scientific method – were explicitly mirrored in many of the project activities. [p.9]